Mutation of Phe318 within the NPxxY(x)5,6F motif in melanin-concentrating hormone receptor 1 results in an efficient signaling activity - Hamamoto, Akie; Horikawa, Manabu; Saho, Tomoko; Saito, Yumiko (Frontiers in Endocrinology, 2012)
Melanin-concentrating hormone receptor 1 (MCHR1) is a G protein-coupled receptor (GPCR) that plays an important role in feeding by coupling to Gaq- and Gai-mediated signal transduction pathways. To interrogate the molecular basis for MCHR1 activation, we analyzed the effect of a series of site-directed mutations on rat MCHR1 function. In the highly conserved NPxxY(x)5,6F domain of GPCRs, the phenylalanine residue is involved in structural constraints; replacement with alanine generally leads to impaired/lost GPCR function. However, Phe-to-Ala (F318A) mutation in MCHR1 had no significant effect on the level of cell surface expression and receptor signaling. By analyzing a further series of mutants, we found that Phe-to-Lys substitution (F318K) caused the most significant reduction in the EC50 value of MCH for calcium mobilization without affecting receptor expression at the cell surface. Interestingly, GTPgS-binding, which monitors Gai activation, was not modulated by F318K. Our results, combined with computer modeling, provide new insight into the role of Phe in the NPxxY(x)5,6F motif as a structurally critical site for receptor dynamics and a determinant of Ga protein interaction.